A new approach to numerical algorithms - Lopes, Ana Paula (2012)
In this paper we developed a new Lanczos algorithm on the Grassmann manifold.  This work comes in the wake of the article by A. Edelman, T. A. Arias and S. T. Smith, “The geometry of algorithms with orthogonality constraints”